2010
DOI: 10.1007/s13163-010-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Any smooth knot $\mathbb{S}^{n}\hookrightarrow\mathbb{R}^{n+2}$ is isotopic to a cubic knot contained in the canonical scaffolding of ℝ n+2

Abstract: Any smooth knot S n → R n+2 is isotopic to a cubic knot contained in the canonical scaffolding of R n+2Abstract The n-skeleton of the canonical cubulation C of R n+2 into unit cubes is called the canonical scaffolding S. In this paper, we prove that any smooth, compact, closed, n-dimensional submanifold of R n+2 with trivial normal bundle can be continuously isotoped by an ambient isotopy to a cubic submanifold contained in S. In particular, any smooth knot S n → R n+2 can be continuously isotoped to a knot co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Observe that a cubical manifold can be subdivided into simplices to become a PL-manifold. M. Boege, G. Hinojosa and A. Verjovsky proved in [2] the following theorem. Theorem 1.2.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Observe that a cubical manifold can be subdivided into simplices to become a PL-manifold. M. Boege, G. Hinojosa and A. Verjovsky proved in [2] the following theorem. Theorem 1.2.…”
Section: Introductionmentioning
confidence: 92%
“…Observe that by construction, v slkm(N ) is well-defined continuous transverse 2-field. By Theorem 3.5, we know that there exists a local transverse 2-vector field v Fm(N ) : F(N ) → G (2,4), such that it is a local transverse 2-field at y ∈ Int(F m (N )) and for y ∈ ∂(S 1 ∪ S 2 ), we have that v Fm(N ) (y) = v slkm(N ) (y).…”
Section: Remember Thatmentioning
confidence: 99%
“…In [2] it was shown that any smooth knot K n : S n → R n+2 can be deformed isotopically into the n-skeleton of the canonical cubulation of R n+2 and this isotopic copy is called cubical n-knot. In particular, every smooth 1-knot S 1 ⊂ R 3 is isotopic to a cubical knot.…”
Section: Introductionmentioning
confidence: 99%
“…In [5] it was shown that any smooth knot S n ∼ K n ⊂ R n+2 can be deformed isotopically into the n-skeleton of the canonical cubulation of R n+2 and this isotopic copy is called cubic knot. In particular, every classical smooth knot S 1 ⊂ R 3 is isotopic to a cubic knot.…”
Section: Introductionmentioning
confidence: 99%